Galactography Combined with Sonogalactography for Improving the Evaluation of Pathological Nipple Discharge - Juan de Dios Berná-Serna; Florentina Guzmán-Aroca; César Leal-Costa; Miguel Alcaraz; Juan de Dios Berná-Mestre (Applied Sciences, 2020)
Diagnosing patients with pathological nipple discharge (PND) is controversial, and therefore a standardized diagnosis algorithm is needed. The objective of this study was to investigate the usefulness of galactography (GL) combined with sonogalactography (SGL) for the evaluation of PND patients. A retrospective study was conducted of 51 patients with PND who were evaluated with GL and SGL. The findings from the galactograms of the patients in this study were assigned to different categories of the Galactogram Image Classification System. Additionally, the sensitivity, specificity, and the positive predictive values and negative predictive values of the GL and SGL tests were calculated, considering the gold standard of pathology diagnosis. The results obtained show that GL combined with SGL improved the diagnostic efficiency of ductal lesions, especially for borderline and malignant lesions. Papilloma was diagnosed in 19 cases, and ductal carcinoma in situ in 8 patients. Conclusions: To the best of our knowledge, this is the first study in which the combination of GL and SGL improves the diagnostic efficiency of ductal lesions of patients with PND. A diagnosis algorithm is recommended for women with PND.